1990
DOI: 10.1073/pnas.87.11.4068
|View full text |Cite
|
Sign up to set email alerts
|

AIDS Kaposi sarcoma-derived cells produce and respond to interleukin 6.

Abstract: Cell lines derived from Kaposi sarcoma lesions of patients with AIDS (AIDS-KS cells) produce several cytokines, including an endothelial cell growth factor, interleukin lf, and basic fibroblast growth factor. Since exposure to human immunodeficiency virus increases interleukin 6 (IL-6) production in monocytes and endothelial cells produce IL-6, we examined IL-6 expression and response in AIDS-KS cell lines and IL-6 expression in AIDS Kaposi sarcoma tissue. The AIDS-KS cell lines (N521J and EKS3) secreted large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
192
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(203 citation statements)
references
References 19 publications
10
192
1
Order By: Relevance
“…The lesions also contain a variable inflammatory and mononuclear cell infiltrate. Studies published beginning in the late 1980s indicated that spindle cells derived from KS lesions could release, proliferate, and/or migrate in response to various growth factors that stimulate angiogenesis, including vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), interleukins -1, -6 and -8, and platelet-derived growth factor (PDGF), and over-express receptors for multiple cytokines [19][20][21][22]. Activation of these receptors stimulates multiple pro-growth and anti-apoptotic pathways via PI3kinase/Akt/mTOR and extracellular receptor kinase (ERK) [23].…”
Section: Developing a Better Understanding Of Ks Pathogenesismentioning
confidence: 99%
“…The lesions also contain a variable inflammatory and mononuclear cell infiltrate. Studies published beginning in the late 1980s indicated that spindle cells derived from KS lesions could release, proliferate, and/or migrate in response to various growth factors that stimulate angiogenesis, including vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), interleukins -1, -6 and -8, and platelet-derived growth factor (PDGF), and over-express receptors for multiple cytokines [19][20][21][22]. Activation of these receptors stimulates multiple pro-growth and anti-apoptotic pathways via PI3kinase/Akt/mTOR and extracellular receptor kinase (ERK) [23].…”
Section: Developing a Better Understanding Of Ks Pathogenesismentioning
confidence: 99%
“…6,7 Of particular interest are the findings that these cells secrete and respond to interleukin-6 (IL-6) and oncostatin M (OSM) suggesting a possible autocrine and/or paracrine growth regulation. 6,[8][9][10] HHV-8 infection may conceivably cause the cytokine production in these cells. 11 It is known that viral genes can transactivate cellular genes; such transactivation is thought to be one of the mechanisms of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Ftirihermore. IL-6 is known to be a growth factor lor multiple myeloma [36,37] and Kaposi's sarcoma [38,39] and-as a eonsequence of polyelonal B cell stimulalion-mighi be related to Ihc increased frequency of B cell malignancies in HIV-infected individuals [40|. Thus, differences in plasma IL-6 levels might result in a differenl risk of developing sueh malignancies.…”
Section: Discussionmentioning
confidence: 99%